Undercover Asian : multiracial Asian Americans in visual culture - Nishime, LeiLani (Urbana [Illinois] : University of Illinois Press, 2014)
Ways to perceive multiracial Asian Americans in popular media.
Multiracial Asian Americans and the myth of the mulatto millennium -- Queer Keanu : the politics of bad acting in the era of don't ask, don't tell -- Tiger Woods and the perils of colorblind celebrity -- Aliens : the interracial family in Battlestar Galactica -- The matrix trilogy and multiraciality at the end of time -- Camp Kimora -- Seeing multiracial.
Includes bibliographical references and index.
Print verison record.
English.
eBooks on EBSCOhost
Keywords: Asian Americans in popular culture -- United States; Multiracial people in popular culture -- United States; Visual culture -- United States; Américains d'origine asiatique dans la culture populaire -- États-Unis.; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; SOCIAL SCIENCE -- Ethnic Studies -- Asian American Studies; Asian Americans in popular culture; Multiracial people in popular culture; United States; Electronic books